Politik pemberdayaan kelompok tani sawit swadaya di Kampung Sialang Palas, kecamatan Lubuk Dalam, Siak - Khairul Anwar; Adianto Adianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This service activity is set in the context of Sialang Palas Village, Lubuk Dalam District, Siak Regency. This area consists of 90% of oil palm plantations but land-use patterns, information and communication technology, decreased purchasing power of farmers, low nutritional status of farmer households. Meanwhile, the influence of local leadership is getting weaker, and Gapoktan institutions are not functioning. In this condition, there was a change in the political behavior of peasants which was initially critical, dynamic, and weakened, eroded by the narrower structure of the local democratic space, and the impact of changes in the national political economy. Therefore, farmer participation in group management needs to be increased. This activity aims to increase the capacity of independent smallholders in managing farmer groups and making decisions through the application of